Efficacy and safety of HDL/apoA-1 mimetics on human and mice with atherosclerosis: a systematic review and meta-analysis. (4th February 2022) - Abudukeremu, A; Li, H; Sun, R; Liu, X; Wu, X; Xie, X; Huang, J; Zhang, J; Bao, J; Zhang, Y
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): the National Natural Science Foundation of China Background: Low high-density lipoprotein cholesterol (HDL-C) level as a residual risk factor of cardiovascular disease (CVD) is still causing concern, although using chemical drugs for raising HDL-C level failed. The effect of high-density lipoprotein/ apolipiproteinA-1(HDL/apoA-1) mimetics on atherosclerosis is controversial. Aim: In this meta-analysis we analyzed the effect of high-density lipoprotein/ apolipiproteinA-1(HDL/apoA-1) mimetics on atherosclerotic lesion both in human and mice. Methods: We systematically searched PubMed, Cochrane, Web of Science and EMBASE databases up to June 6, 2020 for eligible studies using wide search terms and included all the publications meet the including criteria. The methodological quality of the human studies was assessed using Review Manager (RevMan) software (version 5.3.). The methodological quality of the mice studies was assessed by using stair list. WMD(SMD) with 95% CI was used as a measure of the association between HDL/apoA-1 mimetics and plaque regression in human (in mice), after pooling data across trials in a random effect model. Sensitivity and subgroup analyses were used to explore sources of heterogeneity and the effect of potential confounders. STATA (version 14.0) was used to conduct all statistical analyses. Results: We identified 15 randomized controlled trials in which 6 trails including 754 ACS (HDL/apoA-1 mimetics = 414, placebo = 340) patients used for efficacy analysis and all of 15 trails used for safety analysis and 17 controlled trials for animal study. The pooled results showed that the use of HDL/apoA-1 mimetics did not significant decreased the percent atheroma volume(p = 0.494) and total atheroma volume(p = 0.560) in patients with acute coronary syndrome (ACS). However, HDL/apoA-1 mimetics (or gene transfection) was significant associated with all of final percent lesion area, final lesion area and changes in lesion area (SMD, -1.75; 95% CI: -2.21∼-1.29, p = 0.000; SMD, -0.78; 95% CI: -1.18∼-0.38, p = 0.000; SMD: -2.06; 95% CI, -3.92∼-0.2, p = 0.03) in mice. Conclusions: In human, HDL/apoA-1 mimetics cannot significantly improve atheroma volume in artery, although it is safe. However, in animal, the results suggest HDL/apoA-1 mimetics (or gene transfection) can decrease lesion area. So additional studies are needed to further investigate and explain the different efficacy of HDL/apoA-1 mimetic peptides between human and animal.